Vegetation Structure and Damage Level Mangrove Forest in Manomadehe Island, Subdistrict South Jailolo, North Maluku Province - Salim Abubakar; Riyadi Subur; Masykhur Abdul Kadir; Rina Rina; Adi Noman Susanto; Hendrik Suryo Suriandjo (Jurnal Biologi Tropis, 2021)
Mangrove forest is a natural resource typical of tropical coasts, which has multiple benefits with a very broad impact when viewed from social, economic and ecological aspects. Management of natural resources must be very prudent because it takes a long time to be able to recover when damage / extinction has occurred. The purpose of this study was to determine the composition of mangrove species, the structure of mangrove forest vegetation (species density, relative density of species, frequency of species, relative frequency of species, species cover, relative cover of species and important values) and to determine the level of damage. Extraction of mangrove vegetation using the "spot check" method. The transects are drawn perpendicular to the coastline along the mangrove vegetation. The composition of mangrove species were 7 species, namely Rhizophora apiculata, R. stylosa, Bruguirea gymnorrhiza, Ceriops tagal, Sonneratia alba, Xylocarpus granatum and Aegiceras floridum. In the vegetation structure, the highest density and relative density were found in Rhizophora stylosa and the lowest was Xylocarpus granatum. The highest species and relative frequencies were Rhizophora stylosa, R. apiculata and the lowest were Bruguiera gymnorrhiza. The highest type and closure were Sonneratia alba and the lowest was Ceriops tagal. Meanwhile, the highest importance was in Sonneratia alba and the lowest was Xylocarpus granatum. Overall, the density value of mangrove species on Manomadehe Island is 2796 trees / ha so that the condition of the mangrove forests on Manomadehe Island is still in the good category (very dense).